2012
DOI: 10.1093/bja/aes349
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic effects from aortocaval compression at different angles of lateral tilt in non-labouring term pregnant women

Abstract: Patients with ACC can be identified by the CO changes from serial measurements between supine, 15°, or full lateral tilt. Our findings suggest that in non-labouring parturients, ACC is asymptomatic and can be effectively minimized by the use of a left lateral tilt of 15° or greater.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
3
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(61 citation statements)
references
References 30 publications
1
49
3
3
Order By: Relevance
“…8 Hypotension may be compounded by aortocaval compression during SA for CS, particularly if lateral tilt is not adequately applied. 9 In the present study, the odds of experiencing nausea with a minimum-recorded SBP less than 70% of baseline were 2.46 times higher than those in whom SBP was always higher than 70% of the baseline value. There was no difference in the incidence of hypotension between our two groups, and no difference in oxytocin use.…”
Section: Discussioncontrasting
confidence: 42%
“…8 Hypotension may be compounded by aortocaval compression during SA for CS, particularly if lateral tilt is not adequately applied. 9 In the present study, the odds of experiencing nausea with a minimum-recorded SBP less than 70% of baseline were 2.46 times higher than those in whom SBP was always higher than 70% of the baseline value. There was no difference in the incidence of hypotension between our two groups, and no difference in oxytocin use.…”
Section: Discussioncontrasting
confidence: 42%
“…Kuo et al, observed that this biphasic shift towards augmented sympathetic tone in late pregnancy is in part attributed to aortocaval compression by the gravid uterus (16, 144, 145). In these cases, the gravid uterus compresses upon the maternal abdominal aorta and inferior vena cava, resulting in both a decrease in cardiac output and venous return, and eliciting compensatory changes in sympathetic tone (146). …”
Section: The Autonomic Regulation Of Cardiovascular Physiological Adamentioning
confidence: 99%
“…In parallel, there is a drop in peripheral vascular resistances. After the first trimester, the uterus-induced aortocaval compression decreases venous return and alters supine position tolerance [29].…”
Section: Physiological Changesmentioning
confidence: 99%